Cellular and molecular mechanisms underlying extravasation of human Wharton’s jelly mesenchymal stem cells across fetal and adult endothelial cell monolayers - Ebrahim, Neven (2016)
The Wharton’s Jelly (WJ) of human umbilical cord (HU) contains multipotent stem cells (WJ-MSC) which express mesenchymal markers but not hematopoietic markers. WJ-MSC are increasingly being tested for use in stem cell therapy, with intravenous delivery being the preferred route. Fetal stem cells from embryonic germ layers are present in maternal blood and can home to damaged maternal tissues. This study investigates how WJ-MSC cross the fetal and adult endothelial barriers; including the cellular and molecular mechanisms employed. WJ-MSC were isolated from HU (n=27) which were taken from normal term pregnancies after elective Caesarean section. Flow cytometry and immunofluorescence were used to check presence/absenc of mesenchymal versus haematopoietic markers. Cells were induced to become adipocytes, chondrocytes and osteocytes by using specific induction medium. Isolated WJ-MSC were added after labelling with PKH26 to confluent monolayers of isolated human umbilical vein endothelial cells (HUVEC) or commercially bought human uterine microvascular endothelial cells (HUtMEC) at a 1:5 ratio. Cell-cell interactions were monitored with real time microscopy for 24 to 40h. Fluorescence and confocal scanning microscopy, after vascular endothelial (VE) cadherin immunocytochemistry were used for detailed analysis of VE-cadherin junctional occupancy and spatio-temporal location of stem cells. Tyrosine phosphorylation status of VE-cadherin, whether at Tyr685 or Tyr731, at different time points were investigated by immunoblotting whilst levels of vascular endothelial growth factor (VEGF) in the conditional media (CM) were measured by ELISA. Three different isolates were tested, with 3 experimental repeats for all expermints. Statistical analyses were performed with ANOVA (One or Two way). Cells (>95%) from each passage were positive for the mesenchymal markers CD 29, CD 105, CD 90, CD 73 and CD 44. <2% cells showed positivity to the haematopoietic markers CD 34, HLA-DR, CD 14, CD 19 and CD 45. WJ-MSC differentiated into adipocytes, osteocytes and chondrocytes. WJ-MSC displayed exploratory behaviour for a minimum of 30 min on HUtMEC or 60 min on HUVEC with interrogation of paracellular openings before crossing rather than replacing endothelial cells. By 2h, half were found at sub-endothelial positions, with a majority reaching this within 16-22h. There was accompanying loss of junctional VE-cadherin (64.9 + 3.7 %; p<0.001 in HUVEC; 63 + 4.6%; p< 0.001 in HUtMEC) in the endothelial monolayers followed by a return at 16h and increased continuity by 22h (p<0.01 in HUVEC; p<0.001 in HUtMEC). Junctional disruptions were found close to overlying or migrating WJ-MSC. Confocal microscopy confirmed paracellular extravasation. VE-cadherin protein levels matched controls in the early hours (0-2h) and increased after 22h co-culture in both fetal and uterine endothelium. VE-cadherin showed a 2-fold increase in phosphorylation at Tyr685 from 30 min to 2h. P-Tyr731 remained unchanged, similar to untreated endothelial layers, then decreased at 2h and 22h. VEGF levels in WJ-MSC – HUtMEC co-culture supernatants was highest at 2h (88 + 3 pg/ml) and decreased by 22h, reaching negligible levels by 48h. Anti-VEGF blocked Tyr685 phosphorylation but did not affect the decrease in P-Tyr731; this was accompanied by a 25% decrease in transmigration of cells in the first two hours and a 43% decrease in total by 22h. in WJ-MSC – HUtMEC co-cultures. However, in HUVEC-WJ-MSC co-cultures, no VEGF were detected and anti-VEGF did not block Tyr685 phosphorylation and Tyr731 de-phosphorylation. WJ-MSC from term umbilical cords can be easily isolated and expanded in culture. They retain mesenchymal stem cell properties for the passages tested (up to P5) making them a valuable model for studies into mechanisms underlying extravasation. The data obtained suggest that WJ-MSC can influence expression of VE-cadherin, with perturbation during transmigration followed by upregulation and repair once the adlumenal side is reached. There was a similarity in the cellular and molecular mechanisms employed by WJ-MSC in their paracelluar migration across fetal and uterine endothelium, although VEGF may not be the key player in HUVEC interactions. For both endothelial types, WJ-MSC appear to induce phosphorylation events linked with paracellular permeability and de-phosphorylation events normally associated with leukocyte extravasation. The data from the uterine endothelial investigations suggests that fetal stem cells are able to influence paracellular junctional dynamics and strengthens the growing hypothesis that they may also play a role in re-modelling the uterine circulation for fetal advantage. The extra-embryonic WJ-MSC holds the promise of use in restoring junctional maturity and vascular repair in future therapeutic applications.